From Miss Ida's porch - Belton, Sandra; Cooper, Floyd (New York : Aladdin Paperbacks, 1998)
In the evening the residents of Church Street gather on Miss Ida's porch to share memories and hear stories about events in the past, events significant to them as black people.
Keywords: African Americans -- Fiction; Storytelling -- Fiction